PENERAPAN MODEL COOPERATIVE TIPE THINK PAIR SHARE BERBANTU CANVA TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS V DI MI FATHUL IMAN KOTA PALANGKA RAYA - Nova Widya Rahmawati; Rahmad; Muhammad Syabrina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the implementation of the cooperative learning model of the Think Pair Share (TPS) type assisted by Canva and to determine the improvement of student learning outcomes in the IPAS (Natural and Social Sciences) subject in class V at MI Fathul Iman Palangka Raya. This research used a quantitative approach with a Pre-Experimental Design in the form of a One Group Pretest-Posttest Design. The sample consisted of 31 students of class V-A, selected through purposive sampling. Data were collected through observation, tests, and documentation. The learning outcome test data were analyzed using the Shapiro-Wilk normality test, which showed that both pretest and posttest data were normally distributed (Sig. > 0.05). Therefore, the hypothesis was tested using the parametric Paired Sample T-Test. The results showed that the average pretest score was 62.90 and the average posttest score was 79.68. The Paired Sample T-Test result obtained a t value of -12.680 with df = 30 and Sig. (2-tailed) of 0.000 (< 0.05), indicating a significant difference between the pretest and posttest scores. These findings indicate that the application of the cooperative learning model of the Think Pair Share type assisted by Canva has a significant effect on improving student learning outcomes in the IPAS subject.